Strategies in Energy Supply: A Social Network Analysis on the Energy Trade of the European Union - Cemal Zehir; Mustafa Yücel; Alex Borodin; Sevgi Yücel; Songül Zehir (Energies, 2023)
As energy is vital in the sustainability of almost every part of daily life, energy security has become more crucial than ever before. One of the main threats to energy security is a possible disruption along the trade network, which jeopardizes the constant energy supply. The purpose of this research is to identify the relation ties between EU countries in order to clarify the characteristics of the network, such as its crucial actors, vulnerabilities, structural holes, etc., to help achieve some proposals for a more sustainable and secure energy supply. This will help identify the underlying causes of recurring energy crises in the EU and provide insight into developing management strategies for further studies. Following this purpose, we examined the trade network density to clarify typical characteristics of the network, applied degree centrality measures to identify the most central importer and exporter countries, and found the dominance and critical vulnerabilities of actors in the network by using domestic import data of the EU countries. Finally, we recommend some policies and management strategies according to the obtained results and previous literature for further discussion.